2013
DOI: 10.1117/12.2025282
|View full text |Cite
|
Sign up to set email alerts
|

The Debris Disk Explorer: a balloon-borne coronagraph for observing debris disks

Abstract: The Debris Disk Explorer (DDX) is a proposed balloon-borne investigation of debris disks around nearby stars. Debris disks are analogs of the Asteroid Belt (mainly rocky) and Kuiper Belt (mainly icy) in our Solar System. DDX will measure the size, shape, brightness, and color of tens of disks. These measurements will enable us to place the Solar System in context. By imaging debris disks around nearby stars, DDX will reveal the presence of perturbing planets via their influence on disk structure, and explore t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…While many high-contrast mission designs include a Fast Steering Mirror (FSM) upstream of the DM to provide precision pointing correction (e.g. Roberts et al (2013); Chakrabarti et al (2015); Demers et al (2015)), the volume requirements of a CubeSat platform suggest an all-in-one design where the DM provides both pointing and high-order correction. Continuous phasesheet MEMS DM stroke depends on the displacement of adjacent actuators (Bifano et al, 1997); thus, a conservative margin was applied to determine the stroke required to correct for misalignments as well as spacecraft pointing errors using a Blue Canyon XACT attitude determination and control system (ADCS) which were assumed to be ≲ 10″ RMS (Mason et al, 2016).…”
Section: Actuator Strokementioning
confidence: 99%
“…While many high-contrast mission designs include a Fast Steering Mirror (FSM) upstream of the DM to provide precision pointing correction (e.g. Roberts et al (2013); Chakrabarti et al (2015); Demers et al (2015)), the volume requirements of a CubeSat platform suggest an all-in-one design where the DM provides both pointing and high-order correction. Continuous phasesheet MEMS DM stroke depends on the displacement of adjacent actuators (Bifano et al, 1997); thus, a conservative margin was applied to determine the stroke required to correct for misalignments as well as spacecraft pointing errors using a Blue Canyon XACT attitude determination and control system (ADCS) which were assumed to be ≲ 10″ RMS (Mason et al, 2016).…”
Section: Actuator Strokementioning
confidence: 99%
“…Despite an ever increasing number of space missions, there has been renewed interest in recent years for exploring the use of high-altitude balloon flights for nighttime astronomical research. This has resulted in a number of papers discussing possible lighter-than-air (LTA) vehicles and telescope arrangements for optical and infrared observations from non-polar locations [6,15,20,36,43,44]. A self-propelled, highaltitude, long endurance (HALE) stratospheric airship capable of keeping station over a desired geographic location would be a highly attractive platform for a variety of astronomical and other science missions [14].…”
Section: Airshipsmentioning
confidence: 99%
“…The Wallops Pointing system 11 has been used as the baseline for several larger mission concepts. Bryden et al 12 and Roberts et al 13 explored long-duration flights with four channel imaging coupled to 1.1 and 0.75 m telescopes, respectively, and found that tens of debris disks are within range of such missions. Meanwhile, imaging and coronagraph technology has developed to allow more compact and lightweight high-contrast balloon payloads.…”
mentioning
confidence: 99%